DOP27 The fibre fermentative capacity of the gut microbiota is diminished in children with Crohn's Disease and it is independent of disease activity or treatment with exclusive enteral nutrition. (27th May 2021) - Gkikas, K; Logan, M; Milling, S; Ijaz, U Z; Hansen, R; Russell, R K; Gerasimidis, K
Abstract: Background: Induction of clinical remission with exclusive enteral nutrition (EEN), has been associated with accompanying changes in the concentration of short chain fatty acids (SCFA) (a biomarker of fibre fermentation) in faeces of children with Crohn's disease (CD) 1 . Here, we assessed the fibre fermentative capacity of the gut microbiota of children with active CD in vitro, before, during and after EEN and compared with healthy children. Methods: 44 faecal samples from 14 children (female, n=7, age, median [Q1, Q3]: 14.1 [11.1, 15.1] years) with active CD were collected before, during (4 weeks) and at the end of EEN (8 weeks) and after food reintroduction (median [Q1, Q3]: 21 [16, 31] days post-EEN). All children had achieved clinical remission at the end of EEN (weighted Paediatric Crohn's Disease Activity Index <12.5). A single faecal sample was collected from 11 healthy children (female, n=4, age, median [Q1, Q3]: 12.4 [9.6, 13.0] years). 24-hour in vitro batch fermentations were performed using 4 fibre substrates (pectin, high-resistant maize starch, wheat bran and a mixture of the three). Net production of SCFA was measured with gas chromatography. Results: Compared to healthy children, the total production of SCFA was significantly lower in children with CD, for all 4 fibre substrates, and regardless of the study timepoint (Figure 1). Net production of SCFA remained unchanged during EEN and at food reintroduction, and for all fibre substrates (Figure 1). No significant association with levels of faecal calprotectin was observed at any of the timepoints. Acetate production was significantly lower in children with CD compared to healthy children for all fibre substrates except for resistant maize starch (Figure 1). Likewise, except for pectin, production of butyrate was significantly lower in children with CD than healthy controls (Figure 1). Production of propionate did not significantly differ between any of the groups. Legend: Production of SCFA after 24-hour in vitro fermentation of faecal samples from CD and healthy children. Asterisks indicate significant differences. A: before EEN, B: 4-week EEN, C: End of EEN, D: Food reintroduction, HC: Healthy children Conclusion: Fibre fermentative capacity is independent of disease activity in patients with CD and remains lower compared to healthy controls. It might be unlikely that the mechanism of action of EEN is mediated by modulation of fibre fermenting bacteria. Reference: 1. Gerasimidis K, Bertz M, Hanske L, Junick J, Biskou O, Aguilera M, et al. Decline in presumptively protective gut bacterial species and metabolites are paradoxically associated with disease improvement in pediatric Crohn's disease during enteral nutrition. Inflamm Bowel Dis. 2014;20(5):861–71.